The Influence of Geography upon International Relations - Florin Pintescu (Codrul Cosminului, 2014)
Robert D. Kaplan, The Revenge of Geography: What the Map Tells Us About Coming Conflicts and the Battle Against Fate, New York, Random House, 2012, 403 p.